THE ROLE OF SUPPORT ON START-UP SUCCESS: A PLS-SEM APPROACH - Daisy Mui Hung Kee,; Yusmani Mohd Yusoff,; Sabai Khin, (Asian Academy of Management Journal, 2019)
A start-up plays a significant role in the economic growth, employment opportunity, incubators for eco-innovation, and create a new market. Despite their important roles towards the economic and social growth, start-ups face difficulty in sustaining and surviving as the failure rate of start-up range between 50% and 95%, especially in emerging countries such as Malaysia. Therefore, it is important for start-ups in developing countries to identify specific support services that determine their success. In this study, we focus on technology-related, market-related, finance-related, and soft-related supports received by start-ups in Malaysia. The present study has collected data from 500 startups in Malaysia who were recipients of the funding from Malaysia government agencies. To the best of our knowledge, this study provides the first statistical test of how start-ups who were business owners or business partners receiving funding or support from the government agencies view the support system. Based on the analysis, this study provides evidence that support matters to start-up success. Technology-related, finance-related, and soft-related supports hold a significant relationship with the start-up success, while surprisingly, market-related support did not have a significant relationship with start-up success. Our results have extended previous research by highlighting the importance of these supports in driving start-up success and indicating how each dimension of these support services either enhances or inhibits start-up success.